Outcomes of 'unrecognised situation awareness failures events' in intensive care unit transfer of children in a Japanese children's hospital. (24th August 2018) - Aoki, Yoshihiro; Inata, Yu; Hatachi, Takeshi; Shimizu, Yoshiyuki; Takeuchi, Muneyuki
Abstract : Aim: To demonstrate that unrecognised situation awareness failures events (UNSAFE) transfers are associated with poorer outcomes in the intensive care unit (ICU) at a Japanese children's hospital lacking a rapid response system. Methods: This retrospective cohort study was conducted between January 2013 and February 2016. UNSAFE transfers were defined as unplanned in‐hospital ward‐to‐ICU transfers requiring tracheal intubation, vasoactive medications or ≥3 fluid boluses before arrival or in the first 60 min of ICU care. We compared ICU stay duration and mortality between UNSAFE and non‐UNSAFE transfers. Results: There were 2126 admissions to the paediatric ICU during the study period, and 244 cases met the definition of an unscheduled in‐hospital transfer (11.5%). Of these, the number of patients transferred following cardiopulmonary resuscitation, in the UNSAFE group and in the non‐UNSAFE group were 9 (3.7%), 68 (28%) and 167 (68%), respectively. In the UNSAFE group, the number of patients who required tracheal intubation, initiation of vasoactive medications or ≥ 3 fluid boluses in the first 60 min of ICU care or before arrival in the ICU was 61 (90%), 38 (56%) and 9 (13%), respectively. ICU stay duration and mortality were significantly poorer in the UNSAFE group than in the non‐UNSAFE group (9 vs. 4 days, P  < 0.0001; 13 vs. 4.2%, odds ratio = 3.5, 95% confidence interval = 1.2–9.8, P  = 0.020, respectively). Conclusions: Patients who experienced UNSAFE transfers had longer ICU stays and higher mortality, and it may be used as a metric of evaluation of effects of rapid response system implementation.